Hapahari and Handep: Cultural Aspects in Village Head Elections in Central Kalimantan - Haridison, Anyualatha (Political Science Program, Universitas Negeri Semarang, 2021)
The article explores the candidate's practice in village head elections, such as vote-buying, brokerage networks, and cultural aspects. We argue that a candidate's victory is determined by the material aspect only, but there are other practices that candidates use to minimize the mobilization of material resources and even resistance. This research is a case study, bound by time and place, and is holistic. We collected data by relying on observation and interviews with many relevant informants in the Pilkades (village head elections) Tumbang Habaon, Central Kalimantan. Through this study, we found that every candidate has engaged in the practice of buying votes and appointing orang kepercayaan (right-hand man) to reach out to voters. However, the material resource practices we observe are not a determinant of a candidate's victory. We analyzed voters' views that they chose because of the candidates' past actions' concrete manifestations, which reflected the Dayak cultural values, namely Hapahari and Handep. In contrast to previous research, candidates believe more in material and spiritual aspects. We broaden his proposition that the candidate's cultural actions drive voter beliefs without resisting the mobilization of material resources.